Relationship of Lipid Profiles to Stroke Patients: Systematic Review - Nurhayati Puspita, Uci; Septianingrum, Yurike; Wijayanti, Lono; Soleha, Umdatus (Journal of Applied Nursing and Health, 2024)
Background: Stroke is the second leading cause of death and a major contributor to disability worldwide, with the highest prevalence in developing countries. Ischemic stroke is the most common type, caused by blood flow obstruction due to blood clots or fatty plaque accumulation (atherosclerosis). Hemorrhagic stroke, on the other hand, occurs due to blood vessel rupture and bleeding in the brain. This systematic review aims to explore the relationship between lipid profiles and stroke incidence. Methods: This study employed a systematic review approach using the PRISMA methodology. Articles were sourced from databases including Google Scholar, PubMed, ScienceDirect, and Cochrane Library, focusing on publications from 2019 to 2024. Keywords used for the search included "lipid profile," "stroke," "ischemic stroke," and "hemorrhagic stroke." A total of 2,556 articles were identified, and after screening and selection, 9 relevant articles were included for review. Results: The systematic review findings indicate a significant relationship between lipid profiles and the occurrence of stroke. Elevated lipid levels, particularly abnormal cholesterol and triglyceride levels, are associated with an increased risk of ischemic and hemorrhagic strokes. Conclusion: This systematic review confirms a significant association between lipid profiles and stroke incidence. Elevated lipid levels increase the risk of both ischemic and hemorrhagic strokes. Early screening and management of lipid profiles through lifestyle changes and appropriate treatments are essential for stroke prevention. Further research should evaluate the effectiveness of targeted lipid-lowering strategies in reducing stroke risk.